Production performance of HyCole, New Zealand White Rabbits and its reciprocal - Bram Brahmantiyo; Yono C. Raharjo; L. H. Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2017)
New Zealand White rabbits (NZW) has been known as broiler rabbit that has been well adapted in Indonesia. HyCole rabbits were imported from France that were selected for high reproduction and growth rate. This study was aimed to evaluate the productivity of HyCole and New Zealand White rabbits and their reciprocal as the basis to develop broiler rabbit which adaptive to tropical climate. Forty heads of doe (PBPB) and 17 heads of buck (PAPA) of HyCole rabbit, and 30 heads of doe and 6 heads of buck of New Zealand White rabbits (NN) were used. The ration was given according to IRIAP standard ration (18 % CP, 2500 kcal ME/kg and 14 % CF). The diet was provided in the morning and the evening, and drinking water was provided ad libitum. Reproductive performance of does (litter size at birth, litter size at wean, mortality and weekly does body weight) and the kit’s growth performance (weekly body weight from weaning until the age of 20 weeks) were evaluated. Data were analyzed using the SAS program (SAS 2001). Rabbits growth data were periodically analyzed by Gompertz model (Blasco & Gomez 1993). HyCole rabbit which was bred in Indonesia had production performance better than NZW rabbit and PAN crossbred (HyCole bucks x NZW does) had the potential to be bred as superior rabbit adaptive to tropical climate because they had hybrid vigor of the number of litter size at birth and kit’s growth rate.